2021
DOI: 10.3989/ajbm.2605
|View full text |Cite
|
Sign up to set email alerts
|

The Madeiran laurel forest endemic Goodyera macrophylla (Orchidaceae) is related to American orchids

Abstract: Macaronesian laurel forests harbour many herbs and laurophyllous trees with Mediterranean/European or Macaronesian affinities. Traditionally, the origin of these taxa has been explained by the relict hypothesis interpreting these taxa as relics of formerly widespread laurel forests in the European continent and the Mediterranean. We analysed the phylogenetic relationships of the Madeiran laurel forest endemic Goodyera macrophylla (Orchidaceae) using sequences from the nuclear ribosomal DNA Internal Transcribed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Smidt et al ( 2021 ) conducted molecular dating and biogeographical analyses of Goodyerinae based on nuclear ribosomal ITS and plastid mat K sequences. Thiv et al ( 2021 ) identified the phylogenetic location of G. macrophylla , which is the sister group to North American species although it is endemic species of Madeira. However, both papers are less reliable in that they used a small number of genes or introns when analyzing them.…”
Section: Discussionmentioning
confidence: 99%
“…Smidt et al ( 2021 ) conducted molecular dating and biogeographical analyses of Goodyerinae based on nuclear ribosomal ITS and plastid mat K sequences. Thiv et al ( 2021 ) identified the phylogenetic location of G. macrophylla , which is the sister group to North American species although it is endemic species of Madeira. However, both papers are less reliable in that they used a small number of genes or introns when analyzing them.…”
Section: Discussionmentioning
confidence: 99%
“… Goodyera s.l. consists of about 99 species distributed in Africa (Mozambique), Western Indian Ocean Islands, Asia, Southwest Pacific islands, Northeast Australia, Europe, Macaronesia (Madeira), North and Central America and the Caribbean ( Chen et al 2009 ; Zhou et al 2020 ; Govaerts et al 2021 ; Thiv et al 2021 ). It is characterized by an elongate creeping rhizome, a cymbiform lip with a concave-saccate hypochile, sectile pollinia and one stigma.…”
Section: Introductionmentioning
confidence: 99%